The perspectives and dilemmas of the policy of training field educators in the face of ultra-conservatism - Safira Rego Lopes; Cacilda Rodrigues Cavalcanti (Universidade Federal do Norte do Tocantins, 2020)
The Degree in Rural Education is part of the context of public education policies that are connected to rural social movements. However, in face of the advancement of neoliberalism with its recent ultra-conservative version, the operationalization of this course has encountered challenges that are found from the formulation of educational policies in a market perspective to the structures of the State that shape the execution of these policies. Thus, this article aims reflecting on the perspectives and dilemmas of graduation courses in Field Education in the context of advances of ultraconservatism and neoliberalism, based on a bibliographic study. In this sense, the concept of trainer of the Degree in Rural Education is taken as a reference, from the analysis of the relationship between the State, social movements and public policies, seeking to identify the challenges these courses face in the current context so as to carry out its conception. Our reflections lead to the conclusion that the Degree in Rural Education, as formulated by the rural education movement, is threatened in the context of ideological persecution, budget cuts and regulatory frameworks that contradict its prospects for training educators and they can only assert its existence as an action against hegemony.